Smoothing Data Ketinggian Air di Saluran Irigasi Menggunakan Cubic Spline - Anggreni, Anggreni; Rizal, Ahmad Ashril; Yusuf, Siti Agrippina Alodia (JSN : Jurnal Sains Natural, 2025)
The water level data is closely related to the water discharge data in the Pesongoran Kuripan channel in West Nusa Tenggara Province. Daily data is needed by farmers to maintain the quantity of water and the quality of agricultural products. Altitude data is taken daily by irrigation workers, but the data is often available in an incomplete state. This paper aims to correct incomplete data on water level data in irrigation canals using the Cubic Spline Interpolation algorithm. This is due to the nature of the data that depends on the climate (seasonal). Therefore, Cubic Spline can be a solution to incomplete data. The first step, create a set of coordinate points from the primary data.The second step is to create a tridiagonal matrix consisting of a lower triangle matrix, a diagonal matrix and an upper diagonal matrix. The third step is the constant search using Gauss-Jordan elimination. The effectiveness of the Cubic Spline method can be seen from the error of the comparison between the set of coordinate points and the coordinate points of the interpolated results. The smaller the error, the more appropriate the expected result . The results of the study prove the effectiveness of Cubic Spline in missing data.